Understanding the experience of being a father of a pre term newborn interned in a neonatal unit - Cardoso, Maria Vera Lúcia Moreira Leitão; Souto, Kely Cristiane; Oliveira, Márcia Maria Coelho (Rev Rene, 2006)
It is a descriptive, qualitative study that aimed at understanding the experience of being a father of a preterm newborn interned in a Neonatal Intensive Care Unit (NICU). It was accomplished at a public hospital in Fortaleza-Ceará, from November 2004 to January 2005. The subjects of this study were the fathers of six preterm infants who were interned at the NICU. They were interviewed with the following question: What did you feel when you realized that your child would go to a NICU? From this analysis five categories were emerged: Hopelessness and sadness; Fear; Faith and hope; Impotence and Joy. The fathers experienced the whole process with the predominance of the feelings of fear and hope.